Perception and Use of Herbal Medicines Among Clients Visiting Selected Community Pharmacies in Ibadan, Nigeria (2020)
Globally, there is an increasing trend in the use of herbal medicines. Despite, the benefit of its use, herbal medicines are not completely harmless. This study aims to evaluate the perception and use of herbal medicines among clients who visited selected community pharmacies in Ibadan metropolis, Nigeria. A cross-sectional survey was carried out among clients who patronized the selected community pharmacies, using a self-administered questionnaire. Demographic information, as well as perception and use of herbal medicines were evaluated. Data were summarized with descriptive statistics while K-W test was used for ranked variables at P< 0.05. The response rate was 90.7 %. Malaria 113 (58.9 %) was cited as the most common illness treated with herbal medicines. A total of 232 (76.8 %) had score  50.0 % indicating “good” perception on the use of herbal medicine. The level of education of the clients significantly influenced some of their perception towards herbal medicine. This include statement such as herbs can cure all diseases (K-W p=0.011), combination of the conventional drugs and herbs have no side effects (K-W p=0.002), and that side effect of synthetic drugs can be minimized with combination with herbs (K-W p=0.044). Most of the respondents had good perception about herbal medicine use. However, it was notable that the level of education significantly influenced the perception about the use of herbal medicines of some respondents. Public sensitization programme, and health education about the safety of herbal medicines, may be a useful means of improving the use of herbal medicine and reduce potential health risk.